2011
DOI: 10.1097/scs.0b013e318207b507
|View full text |Cite
|
Sign up to set email alerts
|

Human Deciduous Teeth Dental Pulp Cells With Basic Fibroblast Growth Factor Enhance Wound Healing of Skin Defect

Abstract: In this research, we examined the effect on wound healing applying basic fibroblast growth factor (b-FGF) that is approved for clinical use to enhance wound healing and human deciduous teeth dental pulp cells (hDPCs) in clinics, but that have been attracting attention as a novel stem cell source in recent years. Human deciduous teeth were harvested from healthy volunteers, and hDPCs were isolated. We used a nude mouse full-thickness skin defect model and evaluated wound healing by macroscopic view and histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…22 Angiogenesis was found to be improved when endothelial progenitor cells from swine deciduous and permanent teeth were used to treat ischemia in a hind limb ischemia mouse model, as the cells helped to increase the blood supply and contributed to the formation of a new capillary network. 23 Lastly, SHED were reported 24 to help accelerate wound healing when associated with fibroblast growth factor (b-FGF).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Angiogenesis was found to be improved when endothelial progenitor cells from swine deciduous and permanent teeth were used to treat ischemia in a hind limb ischemia mouse model, as the cells helped to increase the blood supply and contributed to the formation of a new capillary network. 23 Lastly, SHED were reported 24 to help accelerate wound healing when associated with fibroblast growth factor (b-FGF).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the use of endothelial progenitor cells derived from dental pulp might represent an alternative approach for the transplantation of autologous endothelial progenitor cells in which cells are obtained by an invasive and potentially painful biopsy procedure. 30 Lastly, Nishino Y et al, 24 showed that the use of SHED, in association with basic fibroblasowth factor (b-FGF), in a nude mouse full-thickness skin defect model significantly accelerated wound healing compared with other groups. This work highlights SHED as a promising stem cell population for future wound healing therapies as well.…”
Section: Discussionmentioning
confidence: 99%
“…PKH26 was chosen to label MSCs according to previous study (17). The choice of PKH26 in this study was attributed to its reported advantages as PKH26 is rapid, simple labeling procedure, achieves bright staining without altering protein and cell function and is physiologically stable for up to 4 months in vivo (18)(19)(20).…”
Section: Modeling and Apoptosis (16)mentioning
confidence: 99%
“…The injection of SHED cells improved the skin damage which demonstrated their potential in skin regeneration. When SHED cells associated in vitro with human mesenchymal stromal cells (hMSCs) were transplanted into a wound in a mouse model, the synthesis of collagen was observed resulting in a similar effect on skin regeneration (Nishino et al, ). These same authors also reported the effects of the interaction between the human dental pulp stem cells from deciduous teeth (hDPSCs) and the basic fibroblast growth factor (bFGF) on skin regeneration suggesting that those cells could be used for treatment of epithelial ulceration.…”
Section: Discussionmentioning
confidence: 99%